Work Life Balance Predicts Burnout Among Sandwich Generation: Keseimbangan antara Pekerjaan dan Kehidupan Pribadi Menjadi Indikator Terjadinya Kelelahan pada Generasi Sandwich - Shinta Isnani Nur Ayuni; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Burnout is a condition of physical, emotional, and mental exhaustion frequently experienced by individuals facing prolonged work and family demands. Specific Background: The Sandwich Generation is particularly vulnerable to burnout because they simultaneously carry financial and emotional responsibilities toward parents and children while maintaining work performance. Knowledge Gap: Previous studies have discussed work-life balance, resilience, and burnout separately, yet limited research has simultaneously examined these variables among the Sandwich Generation in Indonesia. Aims: This study aimed to analyze the relationship of work-life balance and resilience with burnout among the Sandwich Generation in Sidoarjo. Results: This quantitative correlational study involved 105 respondents selected through quota sampling. Multiple linear regression analysis showed that work-life balance was significantly associated with burnout, whereas resilience was not significantly associated. Simultaneously, work-life balance and resilience accounted for 11.5% of burnout variance. Work-life balance emerged as the more dominant predictor of burnout among respondents. Novelty: This study integrates work-life balance and resilience simultaneously in predicting burnout within the Sandwich Generation population, emphasizing the role of structural and role-related factors. Implications: The findings highlight the importance of organizational support, flexible work arrangements, and balanced role management to reduce burnout risk among the Sandwich Generation and support psychological well-being in productive-age workers.Highlights: Role management difficulties were linked to higher emotional exhaustion among multigenerational caregivers. Personal adaptability showed limited association with psychological fatigue in respondents. Structural support and balanced responsibilities were identified as dominant factors related to worker well-being. Keywords: Burnout; Work Life Balance; Resilience; Sandwich Generation; Psychological Well Being